ABIN2 Function Is Required To Suppress DSS-Induced Colitis by a Tpl2-Independent Mechanism - Nanda, Sambit K. (J Immunol, 2018)
The A20-binding inhibitor of NF-κB 2 (ABIN2) interacts with Met1-linked ubiquitin chains and is an integral component of the tumor progression locus 2 (Tpl2) kinase complex. We generated a knock-in mouse expressing the ubiquitin-binding–defective mutant ABIN2[D310N]. The expression of Tpl2 and its activation by TLR agonists in macrophages or by IL-1β in fibroblasts from these mice was unimpaired, indicating that the interaction of ABIN2 with ubiquitin oligomers is not required for the stability or activation of Tpl2. The ABIN2[D310N] mice displayed intestinal inflammation and hypersensitivity to dextran sodium sulfate–induced colitis, an effect that was mediated by radiation-resistant cells rather than by hematopioetic cells. The IL-1β–dependent induction of cyclooxygenase 2 (COX2) and the secretion of PGE(2) was reduced in mouse embryonic fibroblasts and intestinal myofibroblasts (IMFs) from ABIN2[D310N] mice. These observations are similar to those reported for the Tpl2 knockout (KO) mice (Roulis et al. 2014. Proc. Natl. Acad. Sci. USA 111: E4658–E4667), but the IL-1β–dependent production of COX2 and PGE(2) in mouse embryonic fibroblasts or IMFs was unaffected by pharmacological inhibition of Tpl2 in wild-type mice. The expression of ABIN2 is decreased drastically in Tpl2 KO mice. These and other lines of evidence suggest that the hypersensitivity of Tpl2 KO mice to dextran sodium sulfate–induced colitis is not caused by the loss of Tpl2 catalytic activity but by the loss of ABIN2, which impairs COX2 and PGE(2) production in IMFs by a Tpl2 kinase–independent pathway.